An In Vitro Assessment of the Antioxidant Activity of Detarium microcarpum Guill. & Perr. Fabaceae - Dahiru, Mubarak Muhammad; Oni, Abdulhasib Oluwatobi; Danga, James; Alhaji, Aisha Alfa; Jonah, Faith; Hauwa, Alkasim Yahaya; Muhammad, Zainab (Sciences of Phytochemistry, 2024)
Medicinal plants are regarded as important sources of exogenous antioxidants due to their phytoconstituents’ free radical scavenging potential. The present study explores the phytoconstituents and antioxidant activity of n-hexane (HFDM) and chloroform (CFDM) fractions of Detarium microcarpum for potential use in the phytotherapy of oxidative stress-linked ailments. The phytoconstituents were qualitatively determined, while the antioxidant activity was determined by in vitro assays. Alkaloids, saponins, steroids, and flavonoids were detected in both fractions, while glycosides and terpenoids were absent. The HFDM (55.40 ± 2.66 AAE µg/mL) showed a significantly higher total antioxidant capacity than the CFDM (34.84 ± 1.22 AAE µg/mL, p<0.05) at the tested concentration (100 µg/mL) while the CFDM (57.84 ± 2.16 AAE µg/mL) exhibited a significantly higher ferric reducing antioxidant power than the HFDM (46.11 ± 1.91 AAE µg/mL, p<0.05) at the tested concentration (100 µg/mL). In the ferric thiocyanate assay, there was no significant (p>0.05) difference between the HFDM (65.59 ± 2.32%) and CFDM (77.42 ± 2.95%). However, both fractions exhibited significantly higher percentage inhibition than ascorbic acid (9.68 ± 5.41%, p<0.05). Moreover, the HFDM (0.21 ± 0.01 nmol/mL) exhibited a significantly lower MDA concentration than the CFDM (0.66 ± 0.06 nmol/mL) and AA (0.46 ± 0.02 nmol/mL). Additionally, ascorbic acid (0.46 ± 0.02 nmol/mL) showed a significantly lower MDA concentration than CFDM (0.66 ± 0.06 nmol/mL). The n-hexane and chloroform fractions of the plants showed promising antioxidant potential, which might be attributed to the identified phytochemicals that have potential applications in the phytotherapy of oxidative stress-linked diseases.